2020
DOI: 10.1093/ofid/ofaa439.340
|View full text |Cite
|
Sign up to set email alerts
|

297. Lactobacillus: Friend or Foe

Abstract: Background Lactobacillus are low virulence commensal organisms which are commonly found in the human oral cavity, gastrointestinal and genitourinary tracts. Although Lactobacillus bacteremia (LB) is rare, evidence aggregating from case reports has implicated LB in several medical conditions. As such, there is reason to suggest that the presence of these organisms in blood cultures may not be due to spurious contamination, but rather, indicative of clinically meaningful events capable of induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The retrospective studies of Arbarillo et al, Nwanyanwu et al and Yelin et al [60,61,62] suggested that the true prevalence of infections caused by lactobacilli is higher than estimated only on the basis of case reports. In addition, in many of the reports analyzed here it was stated that lactobacilli are often disregarded as infective agents since they are considered culture contaminants [29,40,61].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The retrospective studies of Arbarillo et al, Nwanyanwu et al and Yelin et al [60,61,62] suggested that the true prevalence of infections caused by lactobacilli is higher than estimated only on the basis of case reports. In addition, in many of the reports analyzed here it was stated that lactobacilli are often disregarded as infective agents since they are considered culture contaminants [29,40,61].…”
Section: Discussionmentioning
confidence: 99%
“…Three recent studies analyzed retrospectively the occurrence of infections caused by lactobacilli in two hospitals [60,61] and the intensive care unit (ICU) of a children's hospital [62] and found that numerous cases were recorded in four years, one year and five years, respectively. Albarillo et al [60] reported that a total of 47 patients had growth of L. rhamnosus or L. rhamnosus/casei from different types of specimens, i.e.…”
Section: Investigations On the Frequency Of Lactobacilli Infectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three recent studies analyzed retrospectively the occurrence of infections caused by lactobacilli in two hospitals [ 60 , 61 ] and the intensive care unit (ICU) of a children’s hospital [ 62 ] and found that numerous cases were recorded in four years, one year, and five years, respectively. Albarillo et al [ 60 ] reported that a total of 47 patients had L. rhamnosus or L. rhamnosus/casei growth from different types of specimens, i.e., blood, abdominal fluid, abscess, pleural fluid, bronchial fluid, urine, and sputum.…”
Section: Investigations On the Frequency Of Lactobacilli Infectionsmentioning
confidence: 99%
“…Nwanyanwu et al [ 61 ] reported ten cases of bacteremia by lactobacilli in patients with no declared use of lactobacilli probiotics. These patients required long hospitalization (38.5 ± 27.6 days).…”
Section: Investigations On the Frequency Of Lactobacilli Infectionsmentioning
confidence: 99%